2012
DOI: 10.1097/fjc.0b013e318249171d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethanol Extract of Ginkgo biloba Leaves on the Isolated Rat Heart Work and Mitochondria Functions

Abstract: In this study, we attempted to elucidate whether the effects of ethanol extract of Ginkgo biloba leaves (GBE) observed previously on isolated rat heart mitochondria may be realized in situ (in case of isolated heart perfused under normal conditions and under ischemia-reperfusion). We found that GBE at low concentrations (0.01, 0.05, and 0.1 mL/mL) does not affect the heart rate and parameters of electrocardiogram (ECG) but produces a small increase in the coronary flow. Higher concentration of GBE (0.2 and 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…This findings corroborating with other studies (Baliutyte et al, 2012), that observed PRi increased induced by this extract. Furthermore, both GA and GB also induced PRi increased suggesting that both GA and BB can be responsible by enhance PRi induced by GBE.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This findings corroborating with other studies (Baliutyte et al, 2012), that observed PRi increased induced by this extract. Furthermore, both GA and GB also induced PRi increased suggesting that both GA and BB can be responsible by enhance PRi induced by GBE.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, 10 mg/ml, this extract contains only approximately 3.5% of terpenoids of which are 1.8 % of ginkgolides and 1.69% of bilobalide. In recent study, authors use several concentration of Ginkgo biloba, but not show the concentration of extract in grams (mass unity), difficultly the comparison with our research (Baliutyte et al, 2012).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The above discussed data provided new information about the direct effects of EGb761 on mitochondrial functions in vitro. It is worth mentioning that many investigations including ours (Baliutyte et al 2012) demonstrate cardioprotective, neuroprotective and other effects of EGb761 applied on isolated perfused organs or/and in vivo (according to our unpublished observation, the treatment of rats per os for 7 days with ethanol extract of Ginkgo biloba leaves, GBE, increased the cytochromes aa3 content in liver mitochondria, and some mitochondrial respiratory parameters, n=7-9). Thus, Ginkgo biloba constituents and/or metabolites may reach/enter the cells and mitochondria and may affect the cellular energy metabolism in vivo.…”
Section: Discussionmentioning
confidence: 67%